Does ecological compensation have a spillover effect on industrial structure upgrading? Evidence from China based on a multi-stage dynamic DID approach. (15th September 2021) - Zheng, Qiaoqiao; Wan, Liang; Wang, Shanyong; Wang, Chengyuan; Fang, Wenpei
Abstract: China's rapid economic development has led to increasingly serious environmental problems, such as the deterioration of its ecology in important river basins. Adjusting the industrial structure through the mechanism of ecological compensation (EC) is a key measure for solving this economic and environmental dilemma. Early research on the impact of ecological compensation mechanisms has mainly focused on evaluating their performance in terms of the ecological environment, with little empirical evidence. Therefore, it is necessary to explore the economic effects of ecological compensation mechanisms in order to achieve sustainable economic and environmental development. Based on panel data from the Xin'an River Basin in China from 2009 to 2018, a multistage dynamic difference-in-differences (DID) model was constructed to systematically study the impact of the ecological compensation mechanism on the upgrading of the industrial structure. The research results show that due to the implementation of the policy, the industrial structure in pilot ecological compensation areas tends to be rational and advanced. The ecological compensation policy has dynamic effects on the upgrading of the industrial structure during the different stages of its implementation. This study is conducive to further enriching the relevant theories and practices underlying the study of ecological compensation mechanisms. At the same time, this paper provides operational suggestions for ecological protection, the adjustment of the industrial structure, and the formulation of relevant macroeconomic policies. Highlights: DID model was constructed to explore EC's effect on industrial structure upgrading. Ecological compensation does have spillover effects on the industrial structure. Ecological compensation has dynamic effects on the industrial structure.